Intonational means of expressing finality in Tuvan folklore narration - Ryzhikova, Tatiana R.; Plotnikov, Ilya M.; Dobrynina, Albina A.; Ondar, Choigan G. (The New Research of Tuva, 2025)
The present study is as a continuation of our previous work on Tuvan intonation, which was concerned with prosodic markers as means of structuring a folklore text. The purpose of this article is to examine the manifestation of intonational universals associated with the expression of completeness in Tuvan narrative utterances, which has not previously been subjected to a dedicated analysis employing corpus and statistical methods. The theoretical and methodological basis of the study is formed by the principles that have been established in Russian linguistics, including identifying language-level oppositions between intonational units and a multi-aspect analysis of the utterance as a syntactic unit.The material of the study consists of four audio recordings of Tuvan folklore texts, which were segmented into utterances and annotated using Praat. The resulting corpus was examined in order to identify prosodic characteristics that can be considered significant in terms of expressing completeness of an utterance, with the analysis taking into account both the syntactic structure of the utterances in question and their role in the formation of the folklore text.Several intonation patterns typical of Tuvan folklore texts have been identified and associated with specific communicative functions. This allowed us to demonstrate the opposition of final and non-final, as well as clause-internal and clause-final constituents of the utterances in terms of their intonation. As a result, it is shown that the completeness of an utterance is usually expressed by falling tone and intensity, although there are several examples of a level or rising tone at the end of an utterance. This implies the necessity of a further development of the thought expressed by the utterance. The results are consistent with the authors’ previous studies of the Siberian Turkic languages and support the universality of falling tone marking the completeness of an utterance.
Keywords: Tuvan language; intonation; finality; intonational universal; folklore